A diplomacia cultural na política externa chinesa contemporânea: um estudo de caso sobre a atuação dos Institutos Confúcio - Moreira, Gabriela Sant' Ana (2024)
The objective of this work is to analyze the role of cultural diplomacy in contemporary Chinese foreign policy, through the work of the Confucius Institutes. Thus, this work seeks to answer the following question: what is the role of the Institutes in Chinese cultural diplomacy? To answer the proposed question, this research used bibliographic and documentary analysis. The bibliographic analysis consisted of the analysis of articles and books that present different views on the thematic cut, with Chinese authors who attest to the theme with the internal vision, and also with other authors who analyze from the perspective of countries that are targets of this foreign policy. In addition, the documentary research used official documents, speeches and interviews from the presidency, the Chinese Communist Party, the maintaining institution of the institutes, Hanban, as well as databases on the CIs